The Development of Pets Management System - Chottanom, Anirut (Journal of Applied Informatics and Technology, 2018)
Pet health care such as vaccination, annual health check, cleanliness and treatment on time can help and keep pets healthy and have longevity. Sometimes pet owners forget for pet health care. It is resulting in pets have sickness and death. This research has designed and developed a system to help pet owners to remember the pet activity. The system can record pat activity data. This system is based on a smartphone and personal computers. Also, it can handle data such as date and time of injections record pet's activities, pet's illnesses, pet shop care, and photo gallery. The system can be alerted via email which helps to monitor the activities that will be provided to pet’s owner in the future. When testing the system with a sample of 80 pet owners, owners were satisfied with the system at satisfactory level of 3.65 in average and standard deviation of 0.96.